Fear of missing out (FoMO) and digital well-being: a systematic literature review - Yola Eka Putri; Ifdil Ifdil; Linda Fitria; Berru Amalianita; Rizki Novirson (Jurnal Konseling dan Pendidikan, 2026)
llowing the pandemic, social media usage has increased rapidly. This situation exacerbates the phenomenon of individuals' Fear of Missing Out (FoMO). The purpose of this study is to conduct a systematic synthesis of the relationship between Fear of Missing Out (FoMO) and digital wellbeing in the post-pandemic era, covering research articles published between 2016 and 2024. Data was sorted using the PRISMA method and systematically collected from Scopus, using a Boolean search to identify scientific articles relevant to the research topic. The selected scientific articles were limited to the years 2016 to 2024. After the data screening procedure, twelve empirical studies were selected for further review. The quality of these studies was evaluated using JBI for quantitative research and CASP for qualitative studies. Of these studies, five were classified as high-quality, while seven were categorized as medium-quality. The main synthesis findings identified: (1) psychological mechanisms, specifically social comparison, Separation Anxiety Disorder (SAD), and emotional dysregulation, these variables were found to mediate the effects of FoMO on digital well-being in eleven of the twelve studies; (2) adverse outcomes, including problematic internet use, anxiety, depression, and low academic achievement, were found across all studies, with adolescents and young adults impacted by FoMO; and (3) interventions, six studies explored interventions for individuals with high levels of FoMO, with two providing empirical validation and four providing conceptual explanations. This research provides novel contributions to the field of mental health related to FoMO behavior. The findings of the reviewed studies integrate evidence related to the mechanisms, outcomes, and interventions of FoMO behavior. This review is also linked to three theoretical frameworks: social comparison theory, self-determination theory, and the digital stress model. This allows the data synthesis to focus on critical gaps in longitudinal methodology, cultural inclusivity, and research on intervention effectiveness, while also proposing a testable conceptual model for future research directed at intervening FoMO with counseling and other psychotherapies.